Transcending the Carceral Archipelago: Existential, Figurational and Structurational Perspectives on Power and Control - Green, Simon (Oñati Socio-Legal Series, 2015)
From Foucault (1977) through to Cohen (1985) and Feeley and Simon (1992) criminological thinking about punishment has been dominated by penal rationalities of power and control. This has led to an under-theorised notion of the individual in criminology (Green 2011). As society and penality become increasingly ‘re-emotionalised’ (Karstedt 2011) justice and punishment are invested with a new narrative and expressive dimensions. Drawing on Sartre’s (2010) existential philosophy about choice and authenticity and the social theory of Norbert Elias (2000) and Anthony Giddens (1986) the aim is to locate individual freedom and agency within these wider social conditions and through this begin to provide the basis for a broader conception for criminology of power that is both enabling and liberating as well as oppressive and controlling.